Quadrilateral analysis applied to a city population with anterior openbite - Dhivya Dilipkumar; Dhinahar Sundar Raj; Dheena Dayalan; Poonkuzhali Suresh; R Sugapriya (Wolters Kluwer Medknow Publications, 2020)
Aim: (1) To apply the quadrilateral analysis to adult male and female Chennai population with normal occlusion, (2) To compare the results to Chennai adult male and female with anterior openbite, (3) To evaluate the correlation of the quadrilateral variables and (4) To establish additional parameters to determine an openbite tendency. Materials and Methods: The study was carried out from the values taken from 120 pretreatment lateral cephalograms of the selected Chennai population and divided into two groups. Group A consists of 60 lateral cephalograms of 30 male and 30 female patients with balanced anteroposterior and vertical facial proportion and normal overjet and overbite relationship. Group B consists of 60 lateral cephalograms of 30 male and 30 female patients with anterior openbite and comparision done with 2 groups. Results in normal subjects the lower facial heights are equal. In anterior openbite subjects. The facial heights. The sagittal angle. The maxillary and mandibular sagittal ratios. Lower facial height and sagittal ratio is larger than normal. Results: statistical analysis performed with Version 23(SPSS) and Student's t test were done to describe the mean and standard deviation. To assess the relationship pearson correlation was used.The probability value of 0.05 is consdered as significant. Conclusion: The malformation of the craniofacial structure in anterior openbite subjects resides in the maxillomandibular complex. The overbite depth indicator, the sagittal angle, the maxillary, and mandibular sagittal ratio can be additional parameters in determining an openbite tendency.